Makna Tuturan Ta’aiftam Tafafat Masyarakat Desa Pana Kecamatan Kolbano Kabupaten Timor Tengah Selatan - Boimau, Sanhedri (Universitas Muhammadiyah Surabaya, 2025)
Tonis Ta'aiftam Tafafat is one of the traditional marriage stages of the Pana Village community, Kolbano Sub district, South Central Timor Regency, to deliver the bride to the bridegroom's parents, who have married as customarily, religiously, and governmentally. The purpose of this research is to describe and explain the meaning contained in Tonis Ta'aiftam Tafafat in the Pana Village Community, Kolbano District, South Central Timor Regency. Referring to the problems raised in this study, the theory used is Hermeneutics theory. The method used in this research is descriptive qualitative method. The results of the research and discussion show that in Tonis Ta'aiftam Tafafat in the Pana Village Community, Kolbano Sub district, South Central Timor Regency, there are (1) Meaning of Request; (2) Meaning of Togetherness; and (3) Religious Meaning.